The Shape of Warm Glow: Field Experimental Evidence from a Fundraiser - Jeffrey P. Carpenter (Institute of Labor Economics (IZA), 2018)
Theory commonly posits agents who care both for the level of provision of a public good and the extent to which they personally contribute to the cause. Simply put, agents feel some "warm glow" from the donations they make. I discuss a fundraiser devised to exogenously vary the incentive to give and identify the structural parameters of warm glow. Estimates suggest that for participants claiming warm glow as their primary motivation, its shape is increasing and concave. Nevertheless, welfare analysis suggests that warm glow is unlikely to be the only important factor in the decision to give.
Keywords: H41; D03; D64; C93; 330; public good; altruism; warm glow; structural estimate; philanthropy; pari mutuel lottery; fundraising; field experiment; survey validation